The generals' war : operational level command on the Western Front in 1918 - Zabecki, David T. (Twentieth-century battles., 2018)
The Generals' War is a landmark exploration of the generalship that shaped the very framework of modern warfare as we know it today and provides a comprehensive and detailed analysis on the senior commanders of the Great War.